TUNING FEEDBACK CONTROLLER WITH THE ULTIMATE METHOD - Eko Sarwono; Hendro Priyatman (Suara Teknik : Jurnal Ilmiah, 2010)
A feedback control system is of little value if it is improperly tuned;the analogy to an improperly tuned automobile is intructive. It isimportant to have an understanding of how the controller in afeedback control system should be tuned. One of the all methods fortuning feedback controllers was the ultimade method proposed byZiegler and Nichols. The term ultimate was attached because it is userequired the determination of the ultimate gain (sensitivity) andultimate period for the loop.Keywords: tuning, control.